Cytomegalovirus viral and antibody correlates in young children - Dollard, Sheila C (BMC Res Notes, 2014)
BACKGROUND: Young, healthy children shedding cytomegalovirus (CMV) in urine and saliva appear to be the leading source of CMV in primary infection of pregnant women. FINDINGS: We screened 48 children 6 months – 5 years old for CMV IgG and measured levels of CMV IgG, IgM and IgG avidity antibodies, frequency of CMV shedding, and viral loads in blood, urine, and saliva. Thirteen of the 48 children (27%) were CMV IgG positive, among whom 3 were also CMV IgM positive with evidence of recent primary infection. Nine of the 13 seropositive children (69%) were shedding 10(2)-10(5) copies/ml of CMV DNA in one or more bodily fluid. Among seropositive children, low IgG antibody titer (1:20–1:80) was associated with the absence of shedding (p = 0.014), and enrollment in daycare was associated with the presence of CMV shedding (p = 0.037). CONCLUSIONS: CMV antibody profiles correlated with CMV shedding. The presence of CMV IgM more often represents primary infection in children than in adults. Correlating antibodies with primary infection and viral shedding in healthy children adds to the understanding of CMV infection in children that can inform the prevention of CMV transmission to pregnant women.